AMPK-PPARγ-Cidec Axis Drives the Fasting-Induced Lipid Droplet Aggregation in the Liver of Obese Mice - Li, Hongqiang; Sun, Jian; Li, Bojiang; Jiang, Aiwen; Tao, Jingli; Ning, Caibo; Li, Rongyang; Liu, Honglin (Frontiers in Nutrition, 2022)
Intermittent fasting is one of the most common clinical treatments for the obesity, a main risk factor of the metabolic syndrome which can lead to a variety of diseases. Fasting-induced fat mobilization alters the metabolic state of lipid in the liver, predisposing to increase the hepatic lipid droplet aggregation and triglyceride levels. However, the underlying mechanisms regarding the lipid droplet aggregation in the liver after fasting remains elusive. Here, we report that a lipid droplet surface binding protein Cidec (cell death inducing DFFA like effector C) is activated by AMPK to regulate the hepatic lipid droplet fusion following fasting in obese mice. Specifically, we found that lipid droplets were significantly aggregated in the liver of high-fat-diet and ob/ob mice after 16 and 24 hours of fasting, accompanied by the dramatically up-regulated expression of Cidec. Consistently, overexpression of Cidec in the AML12 cells resulted in the intracellular lipid droplet aggregation. Furthermore, we showed that fasting caused the up-regulated expression of AMPK, which in turn activated the transcription of Cidec through the transcription factor PPARγ. Altogether, our observations reveal that fasting-induced hepatic lipid droplet aggregation is mediated by the AMPK-activated expression of Cidec via PPARγ, extending our understanding about the molecular mechanism of the impact of fasting on the obesity and providing potential targets for the treatment of human obesity.